Business statistics in practice - Bowerman, Bruce L. (McGraw-Hill/Irwin, 2001)
The new edition of Business Statistics in Practice provides a modern, practical, and unique framework for teaching the first course in business statistics. This framework features case study and example- driven discussions of all basic business statistics topics. In addition, the authors have rewritten many of the discussions in this edition and have explained concepts more simply from first principles. The only prerequisite for this text is high school algebra.